Carbon Tax in Taiwan: Path Dependence and the High-Carbon Regime - Kuei-Tien Chou; Hwa-Meei Liou (Energies, 2023)
As it has an export-oriented economy, Taiwan urgently needs to keep up with the growing trends toward carbon taxation. However, making the institution of a carbon tax a reality in Taiwan has proven to be difficult. Since 1998, Taiwan has explored the possibility of putting a tax on carbon many times. Specifically, three main windows of opportunity emerged to adopt a carbon tax during this period; however, all of them failed. This study mainly explores why these three opportunities failed, what structural factors hindered them, and how those structural factors formed path dependence and locked the entire society back onto the existing development track. Firstly, Taiwan’s high-carbon industrial structure has established the rapid growth of energy-intensive industries since the end of the 1990s and has created an economy with high energy consumption and pollution levels. Secondly, this analysis showed that through the combination of government bureaucracy, industry, and the China National Federation of Industries, this brown economy and high-carbon emission structure generated institutional, cognitive, and techno-institutional complex lock-ins, which have led Taiwan to its current path and hindered its transformation. Thirdly, under the above framework, this study further analyzes the contexts and problems that caused the three windows of opportunity to fail. Finally, by linking the economy-first orientation of developmental states, this study identifies structural difficulties and possible breakthrough conditions for newly industrialized/industrializing countries that are undergoing low-carbon transitions.